The Analysis of Rescheduling the Savanna Sumatera Bridge Project Using the Pert Method - Panjaitan, Alfin Lambok Pascatama; Hasibuan, Gina Cynthia Raphita; Anas, M. Ridwan (Universitas Ibn Khaldun Bogor, 2025)
Project schedules are generally created manually, which may lead to delays during the implementation on-site. It is due to the non-inclusion of the uncertainty factor in planning the project schedule. Delays in accomplishing one activity will result in delays in the next one. This study was intended to conduct rescheduling process to minimize the delay in the implementation of the Savanna Sumatera Bridge Project. The study applied PERT method in the rescheduling exercise by using three times conjectures on each project work item, which are: optimistic duration, most likely duration, and pessimistic duration. The results showed that the project was completed in 162 working days with a probability of completion of 99.9%, 34 days faster than the target project duration of 196 working days.